2012
DOI: 10.1667/rr2739.1
|View full text |Cite
|
Sign up to set email alerts
|

Dragon's Blood May Have Radioprotective Effects in Radiation-Induced Rat Brain Injury

Abstract: Dragon's blood is a bright red resin obtained from Dracaena cochinchinensis. It is a traditional medicinal that is used for wound healing and to stop bleeding. Its main biological activity appears to be from phenolic compounds found in Dragon's blood. In this study, the radioprotective effects of Dragon's blood were examined after whole brain irradiation of rats with either 100 MeV/u Carbon (12)C(6+) heavy ions or (60)Co γ-rays. The amounts of radiation-induced oxidative stress, inflammatory cytokines and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Our previous studies revealed that DB has radioprotective properties, including reduction of oxidative stress, inflammatory cytokines and neuronal apoptosis after whole-brain irradiation of rats with either heavy ions or γ-rays [30]. In the present study, the radioprotective effect of DB and DBEs in preventing γ-radiation-induced MDA, and in attenuating the inhibition of SOD, CAT and GSH was assessed in the liver and spleen of male BALB/c mice.…”
Section: Discussionmentioning
confidence: 79%
“…Our previous studies revealed that DB has radioprotective properties, including reduction of oxidative stress, inflammatory cytokines and neuronal apoptosis after whole-brain irradiation of rats with either heavy ions or γ-rays [30]. In the present study, the radioprotective effect of DB and DBEs in preventing γ-radiation-induced MDA, and in attenuating the inhibition of SOD, CAT and GSH was assessed in the liver and spleen of male BALB/c mice.…”
Section: Discussionmentioning
confidence: 79%
“…a high level of polyunsaturated fatty acids contained in the brain making it more liable to oxidative damage which is an important mechanism of rIBI. In some preceding studies, ionizing radiation induced significant oxidative stress levels in neuron cells, characterized by the increase of rOS and malondialdehyde (mDa) in addition to the reduction of antioxidants including reduced glutathione, catalase and superoxide dismutase (SOD) (rola et al, 2007;huang et al, 2012 andXin et al, 2012). rOS scavengers were illustrated to be effective in ameliorating radiationinduced neuronal injury (Xin et al, 2012 andLu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Radiations cause myelosuppression and reduce bone growth in young children. DB and dragons blood resin extract (DBE) (its 50% ethanol extracts) have potential radio-protective properties in mouse bone marrow after 60 Co γ-ray's exposure, which supports their candidature as a potential radio-protective and anti-oxidant agent against DNA damage [10,37]. Cytogenetic studies showed that DB and DBE treatment were highly effective in decreasing both simple and complex chromosomal aberrations.…”
Section: Radio-protective Effect On Bone Marrowmentioning
confidence: 91%
“…DB is a bright red resin [8] due to presence of flavylium chromophores [9], which has ethnomedicinal properties because it contains phenolic compounds [10,11]. The blood-red sap of Croton lechleri was found to contain proanthocyanidins as a major constituent which accounted for up to 90% of the dried weight [12].…”
Section: Introductionmentioning
confidence: 99%